Towards an Archaeological-Realist Foucauldian Analytics of Government - Frauley, Jon (The British journal of criminology, 2007)
Studies of government that build upon the work of French thinker Michel Foucault have become very influential for criminological and sociological research and theorizing. However, because Foucault's archaeological texts - those prior to 1975 - have, in large part, been neglected, many currents within his work that can be used to reformulate, strengthen and extend the analytic of government for the production of criminological knowledge have been left unexplored. This paper attends to the conception of indirect rule elaborated on in Foucault's archaeological texts and to how the ontological position elaborated there is sympathetic to realist metatheory. The paper advances a post-empiricist and realist informed analytic of government that holds government to be a stratified process concerning more than the empirically apprehendable outcomes of management techniques, forms of social action and expertise, indirect mechanisms of rule, socio-political objectives, and the proximity of authorities from regulatory objects. In retrieving the neglected archaeological Foucault and illustrating the realist currents within his work, the paper provides some theoretical preconditions' and metatheoretical coherence' for future investigations of the institutions, practices, processes and objects of social ordering and rule that criminologists and sociologists routinely engage with